Las metodologías utilizadas por los docentes del área de matemáticas y su relación en el proceso enseñanza-aprendizaje de los estudiantes de tercer y cuarto grados del subnivel básica elemental de educación general básica de la escuela Dra. Matilde Hidalgo de Procel No. 2, de la ciudad de Loja, período lectivo 2012-2013 - Curillo Guamán, Silvia Patricia (2015)
The present investigation that turns on: "THE USED METHODOLOGIES FOR THE EDUCATIONAL OF THE AREA OF MATHEMATICS AND THEIR RELATIONSHIP IN THE PROCESS TEACHING-LEARNING OF THE STUDENTS OF THIRD AND QUARTER GRADES OF THE BASIC ELEMENTARY SUBLEVEL OF GENERAL BASIC EDUCATION OF THE SCHOOL DRA. NOBLE MATILDE DE PROCEL Not. 2, OF THE CITY DE LOJA, PERIOD LECTIVO 2012-2013", one worked with the general following objective: To contribute to improve the methodological procedure used by the educational ones in mathematics area and their relationship in the process teaching-learning of the students of third and quarter grade of the sublevel basic stocking of General Basic Education of the School "Dra. Matilde Hidalgo of Procel No.2, of the city of Loja, period elective 2012-2013." The same one that helps to the you elucidate of the topic in study, Likewise it was applied different methods: scientific, inductive-deductive, descriptive, analytic-synthetic, the same ones that helped to secure the knowledge and focuses inside the learning process, previó to this investigative process a survey the same one was applied that was directed to the educational ones and students. So that they give to know the different approaches on the methodologies used in mathematics area; it is hence that he/she thought about a hypothesis to verify of agreement with the poured opinions of the actors; of this whole work of suggestive investigation you ended up concluding that the traditional forms of teaching the mathematics are not the appropriate one to arrive since to effective knowledge in the students the educational ones they don't carry out an effort to innovate and to create according to their creative capacity in the mathematics teaching as it is the use of TIC's like half of teaching of the mathematics, because in accordance with their own words and demonstrating in the carried out surveys a conformism exists; for that which is recommended through the address of the School it is either provided of all material type written or spoken with the purpose that the students are the main characters in acquiring the knowledge given by their teachers so that at last it is a complement in their process of assimilating their learning.